Modelo para controle estatístico de processos de desenvolvimento de software (CEP-S) - Patricia Correa Fonseca (2010)
Considering the importance of software industry in the national market, the fact that it is mostly composed of small and medium enterprises (SMEs) and based on the belief that the advancement of this industry occurs, in part, by improving quality and productivity we propose here a model for the application of a Statistical Process Control (SPC) to software development by SMEs. The SPC uses statistics to manage theproduction process, to continually improve quality by reducing the variability of the control parameters and to support decision making by top management. Its main purpose is to diagnose whether the process is under the influence of assignable causes that need to be investigated and eliminated. The model proposes a set of quality characteristics to be monitored for certain processes, and the control charts most appropriatefor each case and suggestions for choosing the control parameters. These elements are organized in a method proposed in the model, providing a framework flexible but with pre-defined choices, to facilitate the application of SPC by SMEs, enabling their initial forays in statistical control activities.